A Novel Micro Cold Atmospheric Plasma Device for Glioblastoma Both In Vitro and In Vivo - Chen, Zhitong (Cancers (Basel), 2017)
Cold atmospheric plasma (CAP) treatment is a rapidly expanding and emerging technology for cancer treatment. Direct CAP jet irradiation is limited to the skin and it can also be invoked as a supplement therapy during surgery as it only causes cell death in the upper three to five cell layers. However, the current cannulas from which the plasma emanates are too large for intracranial applications. To enhance efficiency and expand the applicability of the CAP method for brain tumors and reduce the gas flow rate and size of the plasma jet, a novel micro-sized CAP device (µCAP) was developed and employed to target glioblastoma tumors in the murine brain. Various plasma diagnostic techniques were applied to evaluate the physics of helium µCAP such as electron density, discharge voltage, and optical emission spectroscopy (OES). The direct and indirect effects of µCAP on glioblastoma (U87MG-RedFluc) cancer cells were investigated in vitro. The results indicate that µCAP generates short- and long-lived species and radicals (i.e., hydroxyl radical (•OH), hydrogen peroxide (H(2)O(2)), and nitrite (NO(2)(−)), etc.) with increasing tumor cell death in a dose-dependent manner. Translation of these findings to an in vivo setting demonstrates that intracranial µCAP is effective at preventing glioblastoma tumor growth in the mouse brain. The µCAP device can be safely used in mice, resulting in suppression of tumor growth. These initial observations establish the µCAP device as a potentially useful ablative therapy tool in the treatment of glioblastoma.